Micro-CT visualization of a promastigote secretory gel (PSG) and parasite plug in the digestive tract of the sand fly Lutzomyia longipalpis infected with Leishmania mexicana. - Martin J R Hall (Public Library of Science (PLoS), 2021)
Leishmaniasis is a debilitating disease of the tropics, subtropics and southern Europe caused by Leishmania parasites that are transmitted during blood feeding by phlebotomine sand flies (Diptera: Psychodidae). Using non-invasive micro-computed tomography, we were able to visualize the impact of the laboratory model infection of Lutzomyia longipalpis with Leishmania mexicana and its response to a second blood meal. For the first time we were able to show in 3D the plug of promastigote secretory gel (PSG) and parasites in the distended midgut of whole infected sand flies and measure its volume in relation to that of the midgut. We were also able to measure the degree of opening of the stomodeal valve and demonstrate the extension of the PSG and parasites into the pharynx. Although our pilot study could only examine a few flies, it supports the hypothesis that a second, non-infected, blood meal enhances parasite transmission as we showed that the thoracic PSG-parasite plug in infected flies after a second blood meal was, on average, more than twice the volume of the plug in infected flies that did not have a second blood meal.